Aerobic Glycolysis Is Essential for Normal Rod Function and Controls Secondary Cone Death in Retinitis Pigmentosa - Lolita Petit; Shan Ma; Joris Cipi; Shun-Yun Cheng; Marina Zieger; Nissim Hay; Claudio Punzo (Cell Reports, 2018)
Aerobic glycolysis accounts for ∼80%–90% of glucose used by adult photoreceptors (PRs); yet, the importance of aerobic glycolysis for PR function or survival remains unclear. Here, we further established the role of aerobic glycolysis in murine rod and cone PRs. We show that loss of hexokinase-2 (HK2), a key aerobic glycolysis enzyme, does not affect PR survival or structure but is required for normal rod function. Rods with HK2 loss increase their mitochondrial number, suggesting an adaptation to the inhibition of aerobic glycolysis. In contrast, cones adapt without increased mitochondrial number but require HK2 to adapt to metabolic stress conditions such as those encountered in retinitis pigmentosa, where the loss of rods causes a nutrient shortage in cones. The data support a model where aerobic glycolysis in PRs is not a necessity but rather a metabolic choice that maximizes PR function and adaptability to nutrient stress conditions.